(untitled) (Fiep Bulletin - online, 2019)
Studies point to the association of periodontitis and obesity in young adults, and the clinical parameters in theanthropometric and periodontal evaluation diversify the results. Objective: To evaluate the association of periodontitis andobesity in young adults in a city of Alagoas, Brazil. Material and method: The sample (n = 63) of young adults with mean age of28.90 (± 7.03), with at least 14 teeth and excluded the users of orthodontic appliance, smokers, diabetics, those who made use ofantibiotic in the last three months, pregnant and lactating. Body mass index (BMI) and waist circumference (WC) wereanthropometric parameters and for evaluation of periodontitis, probing depth (PS), clinical insertion level (NIC) and bleedingprobing (SS). The study was divided into two groups, that is, those without obesity and those with obesity. Descriptive analysiswas used, and in the inferential statistics, the Chi-square test and Student’s T test were used. Differences were consideredsignificant with p value <0.05. Results: 53.96% obese were found using CA and 52.39% obese with BMI. In the periodontalevaluation of the group with obesity, the depth of probing (PS) = 1.80 ± 0.50, clinical insertion level (NIC) = 1.78 ± 0.54 associatedwith bleeding at the probing (SS) = 25, 52 ± 18.59, p value <0.05. The study found (73.02%) individuals without periodontitis,61.76% in the obesity group (31.31 ± 4.78). With periodontitis (26.98%), 76.47% were in the obesity group (31.58 ± 5.88), thedifference being statistically significant p <0.05. Conclusion: In view of the results, it is possible to affirm that there is association ofperiodontitis and obesity in obese young adults.